Emotional Imprints of War : A Computer-Assisted Analysis of Emotions in Dutch Parliamentary Debates, 1945-1989 - van Lange, Milan (2023)
Historical research can be enhanced by methods and resources from various disciplines, ranging from psychology to computer linguistics. With a creative and innovative perspective on ›things we think we know‹, Milan van Lange presents a computer-assisted historical investigation into the role of emotions in dealing with consequences of World War II in the Netherlands. By ›emotion mining‹ digitised sources, van Lange shows where emotions were present and how they were expressed and discussed in the political engagement with people who experienced long-term effects of the war, such as former collaborators and war criminals, the resistance, and war victims.